Pengaruh Promosi, Citra Perusahaan Dan Tingkat Religiusitas Nasabah Terhadap Loyalitas Nasabah BPRS Tanggamus - Agus Behaki (Dinar Islamic Review, 2021)
This study aims to examine and analyze the effect of promotion, corporate image, and the level of customer religiosity on customer loyalty at Tanggamus Syariah Bank. This research is quantitative research with a descriptive approach. The population in this study is customers who open savings accounts at Tanggamus Syariah Bank. Sampling was done by using an accidental sampling technique with the criteria of a customer who opened savings account at Bank Syariah Tanggamus aged 17 - 50 years as many as 120 respondents. Data analysis used Multiple Linear Regression with SPSS 17.0 Program. The results of this study indicate that partially and sumultanly promotion, company image, and level of customer religiosity have a positive effect on customer loyalty.